The Influence of Barbie Movies on Female Beauty Standards: a Social Cognitive Perspective - Abdillah Nugroho; Gadis Laylarustu Suharjo (EduInovasi: Journal of Basic Educational Studies, 2025)
Film as a visual media has great power in shaping and directing the audience's perception. A person's cognition can be influenced by what we get and receive in social reality. The purpose of this study was to understand how Barbie movies portray beauty and how this may influence the way children view beauty.This study uses a mixed method research method. This method combines quantitative research and qualitative research that focuses on an in-depth analysis of the beauty standards conveyed in the Barbie film and the influence of the Barbie film on women's beauty standards, especially children. The sampling method for this study was census sampling with 36 respondent. Data sources were obtained from questionnaires and in-depth interviews. Data analysis techniques using simple regression analysis. results Barbie movie influences the perception of beauty standards in children, accordance a simple regression analysis showing that the Barbie movie variable has a sig value of 0.01 <0.05 so that all variables can be stated to have a significant effect on women's beauty standards. then 28.2% of respondents' beauty standards are influenced by Barbie movies. Through social cognitive theory, films explain that children learn based on what they observe and then they will imitate these actions, where children watch Barbie movies, in the process they will learn about the values ​​of beauty by seeing how Barbie characters are depicted in the film. Barbie 2023 movies can influence child development in several ways, namely through attention, retention, and motivation.